1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
|
# -*-octave-*- Put Emacs into octave-mode
# State specification (Reactor_state.txt)
# Generated by MTT at Fri Mar 3 11:52:23 GMT 2000
###############################################################
## Version control history
###############################################################
## $Id$
## $Log$
## Revision 1.2 2000/12/28 18:52:25 peterg
## Updated for new formats
##
## Revision 1.1 2000/12/28 17:09:55 peterg
## To RCS
##
###############################################################
|
>
>
>
|
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
|
# -*-octave-*- Put Emacs into octave-mode
# State specification (Reactor_state.txt)
# Generated by MTT at Fri Mar 3 11:52:23 GMT 2000
###############################################################
## Version control history
###############################################################
## $Id$
## $Log$
## Revision 1.3 2003/06/06 06:38:31 gawthrop
## Made compatible with current MTT.
##
## Revision 1.2 2000/12/28 18:52:25 peterg
## Updated for new formats
##
## Revision 1.1 2000/12/28 17:09:55 peterg
## To RCS
##
###############################################################
|
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
|
## Solve for the steady-state concentrations
## Solve for ca - a quadratic.
a = k_3*e_3; #ca^2
b = k_1*e_1 + f_s; #ca^1
c = -c_0*f_s;
c_a = (-b + sqrt(b^2 - 4*a*c))/(2*a);
## solve for c_b
c_b = c_a*k_1*e_1/(f_s+k_2*e_2);
#States (masses)
x1 = c_a*v_r;
x2 = c_b*v_r;
#Thermal state
x3 = c_p*t_s*v_r;
#Steady-state state q needed to achieve steady-state t_s
q_s = -((t_0-t_s)*c_p*f_s + e_1*h_1*k_1*x1 + e_2*h_2*k_2*x2 + e_3*h_3*k_3*x1^2);
## The two inputs at steady-state
u1 = f_s;
u2 = q_s;
## Load up the states
## Removed by MTT on Thu Dec 28 18:46:20 GMT 2000: mttx(1) = x1;
|
|
|
|
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
|
## Solve for the steady-state concentrations
## Solve for ca - a quadratic.
a = k_3*e_3; #ca^2
b = k_1*e_1 + f_s; #ca^1
c = -c_0*f_s;
c_a = (-b + sqrt(pow(b,2) - 4*a*c))/(2*a);
## solve for c_b
c_b = c_a*k_1*e_1/(f_s+k_2*e_2);
#States (masses)
x1 = c_a*v_r;
x2 = c_b*v_r;
#Thermal state
x3 = c_p*t_s*v_r;
#Steady-state state q needed to achieve steady-state t_s
q_s = -((t_0-t_s)*c_p*f_s + e_1*h_1*k_1*x1 + e_2*h_2*k_2*x2 + e_3*h_3*k_3*pow(x1,2));
## The two inputs at steady-state
u1 = f_s;
u2 = q_s;
## Load up the states
## Removed by MTT on Thu Dec 28 18:46:20 GMT 2000: mttx(1) = x1;
|